Oxydation de Fe2+ par O3 en réacteur semi-continu parfaitement agité - André Schreiber (CHIMIA)
Ferrous ion oxidation by ozonised air was carried out in a laboratory well-mixed semi-flow batch reactor. Ozone transfer is shown to proceed according to Astarita’s fast reaction regime. Experimental data are compared to figures obtained by means of the reactor model equation, the use of which is made very simple by introducing a dimensionless group (J), which is directly related with the ozone reaction efficiency. A method is thereby established for the determination of the interfacial mass transfer area as a function of agitation and superficial gas velocity.